(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
It is summarized that the acquisition of non-formal education by dentistry students has a number of features, including the information filling of basic education, the technological complexity of modern dental services, the high cost of educational programs for dentists. The analysis of students’ awareness about non-formal education was carried out based on the results of a questionnaire at Danylo Halytsky Lviv National Medical University, Ivano-Frankivsk National Medical University, Lviv Medical University, I. Ya. Horbachevsky Ternopil National Medical University. It was found that 62% of the surveyed students do not receive non-formal education. Regarding their awareness about non-formal education resources, we found a match in all three stakeholder groups – students, teachers, employers. Resources are selected as priorities: Prometheus, Coursera, Udemy, edX.org, Khan Academy, navychka. Of those students who use electronic resources of non-formal education, only 13.6% allocate more than four hours a week. The orientation of students is considered according to the priority motivation for educational activities, directed to: self-improvement; professional self-improvement; communication and interaction, expanding one’s social space. Four priorities have been identified: 50% determined that the purpose of obtaining an education is to improve knowledge and skills in the field of study, 36% – personal development, 30% – acquisition of skills and abilities outside the field of study; 27% – expansion of the sphere of communication. An important indicator for characterizing the orientation was the definition of the desired subject of non-formal education programs: 40.5% of survey participants chose business and entrepreneurship. As for the important criteria in the choice, 66% chose a flexible study schedule, 54% chose the ratio of the price of the study and its potential usefulness; 36% – personally attractive programs.